(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
Chitralina undulata gen. n. sp. n. (Foraminiferida) has been found for the first time in the Permian successions of Karakorum (Pakistan). Biostratigraphic analysis based on fusulinids, brachiopods, conodonts and small foraminifers pointed out that Chitralina undulata gen. n. sp. n. occurs from the Kubergandian to the Late Murgabian-Midian. Morphologically, Chitralina undulata gen. n. sp. n., is comparable to Rectostipulina quadrata Jenny-Deshusses, 1985, differing from it by means of the thickness and composition of the test and for the presence of marked longitudinal costae. The stratigraphic range of Rectostipulina quadrata spans the Midian-Dorashamian time-interval. The new genus Chitralina is very similar to the Permian genus Giraliarella Crespin, differing from it by means of the absence of transverse growth constrictions. The new family Chitralinidae fam. n., is also described herein.